2007
DOI: 10.1051/alr:2007029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-timeArtemiaspp. feeding in larvae and different rearing environments in juveniles of common barbel (Barbus barbus) on their growth and survival under intensive controlled conditions

Abstract: The effect of short-time Artemia spp. feeding on growth performance and cumulative survival rate of barbel (Barbus barbus) larvae were studied under controlled aquaria conditions during the 21-day larval period. Three different diets (presenting reduced Artemia feeding) were tested for first exogenous nutrition of larvae (since 13 days post hatch):(1) artificial feed (Asta); (2) Artemia nauplii for 7 days followed by artificial feed; (3) Artemia nauplii for 14 days followed by artificial feed. The longer perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
2
19
1
2
Order By: Relevance
“…Stripping frequency, egg and sperm production in captive females and males of common barbel (Barbus barbus) during the first reproductive season. Different letters within a column indicate differences in all parameters among the months (phases) of reproductive season (P < 0.05) Our study confirmed the previous observations that live feed is not an essential diet for larvae in common barbel at the start of exogenous feeding (Wolnicki and Górny, 1995;Policar et al, 2007). This fact is caused by relatively advanced ontogenic development of barbel larvae at the beginning of exogenous nutrition compared to larvae of other cyprinids (Peňáz, 1971(Peňáz, , 1973Fiala and Spurný, 2001;Policar et al, 2007;Wolnicki et al, 2009).…”
Section: Effect Of Sex On Growth Ratesupporting
confidence: 89%
See 3 more Smart Citations
“…Stripping frequency, egg and sperm production in captive females and males of common barbel (Barbus barbus) during the first reproductive season. Different letters within a column indicate differences in all parameters among the months (phases) of reproductive season (P < 0.05) Our study confirmed the previous observations that live feed is not an essential diet for larvae in common barbel at the start of exogenous feeding (Wolnicki and Górny, 1995;Policar et al, 2007). This fact is caused by relatively advanced ontogenic development of barbel larvae at the beginning of exogenous nutrition compared to larvae of other cyprinids (Peňáz, 1971(Peňáz, , 1973Fiala and Spurný, 2001;Policar et al, 2007;Wolnicki et al, 2009).…”
Section: Effect Of Sex On Growth Ratesupporting
confidence: 89%
“…Different letters within a column indicate differences in all parameters among the months (phases) of reproductive season (P < 0.05) Our study confirmed the previous observations that live feed is not an essential diet for larvae in common barbel at the start of exogenous feeding (Wolnicki and Górny, 1995;Policar et al, 2007). This fact is caused by relatively advanced ontogenic development of barbel larvae at the beginning of exogenous nutrition compared to larvae of other cyprinids (Peňáz, 1971(Peňáz, , 1973Fiala and Spurný, 2001;Policar et al, 2007;Wolnicki et al, 2009). Fast growth and high survival rate could be achieved under controlled conditions if the used artificial feed met the nutrient requirements of barbel larvae (Wolnicki and Górny, 1995;Fiala and Spurný, 2001;Policar et al, 2007).…”
Section: Effect Of Sex On Growth Ratesupporting
confidence: 89%
See 2 more Smart Citations
“…Improperly chosen thermal conditions as well as their fluctuations either delay spawning or cause gametes to mature with defects (Wang et al, 2010;Targońska et al, 2010Targońska et al, , 2012Nowosad et al, 2014a). Final gamete maturation, especially in cyprinids, is induced by hormonal stimulation (Yaron, 1995;Policar et al, 2007; (Kahkesh et al,2010;Targońska et al, 2011b). The bottleneck of this process is the induction of ovulation, whose rate under controlled conditions in barbel is usually about 10% or lower.…”
Section: Introductionmentioning
confidence: 99%